1984
DOI: 10.1007/bf01852393
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cytologic and biochemical properties between liver cells isolated from adult rats by trypsin perfusion and those isolated by collagenase perfusion

Abstract: Primary cultures of liver cells isolated from adult rats by trypsin and collagenase perfusion techniques were carried out to compare cytologic and biochemical properties between the differently prepared cells. Trypsin-dispersed cells consisted of comparatively smaller cells, whereas collagenase-dispersed cells consisted of larger cells. The cell attachment efficiency on culture day 1 was about twice as high in the liver cells prepared with collagenase than those prepared with trypsin. Mature hepatocytes isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

1985
1985
1990
1990

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 21 publications
2
6
0
Order By: Relevance
“…The attached cells were polygonal cells with granular cytoplasm (mature hepatocytes), which arranged themselves to form cords and clusters, as reported previously [9]. Even after change to the serum-free basal medium following the 1-h attachment period, the attached hepatocytes survived well.…”
Section: Resultssupporting
confidence: 79%
“…The attached cells were polygonal cells with granular cytoplasm (mature hepatocytes), which arranged themselves to form cords and clusters, as reported previously [9]. Even after change to the serum-free basal medium following the 1-h attachment period, the attached hepatocytes survived well.…”
Section: Resultssupporting
confidence: 79%
“…In the PB-treated cultures, ppm (Kitagawa et al, 1984). On the other hand, we have also observed that PB causes a dose-dependent increase in the number of marker-chromosome-positive and GGT-positive cultures in the 3'-Me-DABinitiated primary rat liver cell cultures within the dose range of 0.75 to 3 m~, and that the optimal concentration of PB is 1.5 m~ for such promotion (Miyazaki et al, 1985). In this study, therefore, the putative preneoplastic epithelial-type cell lines, which were derived from the 3 '-Me-DAB-initiated cultures of normal adult rat liver cells, were treated with PB at the optimal concentration of 1.5 m~.…”
Section: Resultssupporting
confidence: 53%
“…Four-milliliter and 10-ml aliquots of the cell suspensions were inoculated into 60-and 100-ram Falcon plastic dishes, respectively, and cultured in a humidified atmosphere of 5% CO2 and 95% air at 37°C. To enhance the attachment efficiency of inoculated hepatocytes, dexamethasone and insulin were added to the cultures at 10 ~tM and 10 ~tg/ml, respectively, during only the first 24 h [21]. Following the 1-day attachment period, the culture medium was replaced by the drug-supplemented basal media, or the basal medium supplemented with or without 0.5% DMSO for control cultures.…”
Section: Preparation and Primary Culture Of Isolated Hepatocytesmentioning
confidence: 99%
“…However, after a few days in culture, the hepatocytes enter a period of degeneration and most of the measured liver functions begin to decline rapidly [1,2,21]. Such a rapid and consistent loss in cell function and viability makes it difficult to perform experiments in which cells are to be incubated for long periods of time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation